2015
DOI: 10.1117/1.jbo.20.5.051022
|View full text |Cite
|
Sign up to set email alerts
|

Combination of low level light therapy and nitrosyl-cobinamide accelerates wound healing

Abstract: Low level light therapy (LLLT) has numerous therapeutic benefits, including improving wound healing, but the precise mechanisms involved are not well established; in particular, the underlying role of cytochrome C oxidase (C-ox) as the primary photoacceptor and the associated biochemical mechanisms still require further investigation. We previously showed the nitric oxide (NO) donating drug nitrosyl-cobinamide (NO-Cbi) enhances wound healing through a cGMP/cGMP-dependent protein kinase/ERK1/2 mechanism. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
(34 reference statements)
0
14
0
1
Order By: Relevance
“…Although other units in the electron transfer chain, such as complexes I-IV and succinate dehydrogenase also show increased activity as a result of PBM, CCO is still believed to be one of the primary photoacceptors. This notion is supported by the fact that low-level light irradiation such as PBM causes increased oxygen consumption, and is bolstered by the fact that the majority of oxygen consumption occurs at complex IV, and moreover that the addition of sodium azide, a CCO inhibitor, abrogates the effects of PBM [10,11]. Moreover, rho-zero cells that lack functional mitochondria do not respond to PBM, in the same way as their wild-type counterparts [12].…”
Section: Mechanisms Of Pbmmentioning
confidence: 99%
See 1 more Smart Citation
“…Although other units in the electron transfer chain, such as complexes I-IV and succinate dehydrogenase also show increased activity as a result of PBM, CCO is still believed to be one of the primary photoacceptors. This notion is supported by the fact that low-level light irradiation such as PBM causes increased oxygen consumption, and is bolstered by the fact that the majority of oxygen consumption occurs at complex IV, and moreover that the addition of sodium azide, a CCO inhibitor, abrogates the effects of PBM [10,11]. Moreover, rho-zero cells that lack functional mitochondria do not respond to PBM, in the same way as their wild-type counterparts [12].…”
Section: Mechanisms Of Pbmmentioning
confidence: 99%
“…One of the first human trials of tPBM for AD to be reported, was reported by Saltmarche et al [149] who treated a case series of five patients diagnosed with mild to moderately severe dementia (Mini-Mental State Exam, MMSE, scores of [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The study used the Vielight alpha (810 nm, 10 Hz pulsed, LEDs) that combines transcranial plus intranasal PBM to treat the cortical nodes of the default mode network (bilateral mesial prefrontal cortex, precuneus/posterior cingulate cortex, angular gyrus, and hippocampus).…”
Section: Clinical Trials Of Pbm In Ad and Dementiamentioning
confidence: 99%
“…Low‐level light therapy (LLLT) is a promising modality for the treatment of various conditions, including stroke, myocardial infarction, spinal cord injury, degenerative disorders, and traumatic brain injury . LLLT has been found to exert significant biological effects in cell cultures, as well as in vivo , in animal models and in clinical settings .…”
Section: Introductionmentioning
confidence: 99%
“…LLLT has been found to exert significant biological effects in cell cultures, as well as in vivo , in animal models and in clinical settings . LLLT exerts potent anti‐inflammatory, anti‐edema, and pro‐angiogenetic effects , and can facilitate wound healing by stimulating the proliferation of dividing cells . The beneficial effects of LLLT on new synaptic connections have been shown to contribute to neural repair processes during the reorganization of brain tissues .…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de existirem diversos estudos in vitro, animais e clínicos que demonstrem seus efeitos benéficos, como: aumento da neovascularização, promoção da angiogênese, aumento da síntese de colágeno e promoção da cicatrização de feridas agudas e crônicas, os mecanismos celulares e moleculares de ação da LLLT/PBM são esclarecidos apenas em alguma extensão130 . Está razoavelmente bem compreendido que as mitocôndrias sejam o principal alvo intracelular da luz vermelha visível e NIR, que são Muitos fatores de transcrição são regulados por alterações no estado redox celular.…”
unclassified